PENGARUH FASILITAS KERJA DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR KEMENTERIAN KELAUTAN DAN PERIKANAN (Badan Karantina Ikan, Pengendalian Mutu, Dan Keamanan Hasil Perikanan Kelas 1) - Anggriani Husain (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2024)
This research aims to determine the magnitude of the influence of work facilities (X1) and workload (X2) on job satisfaction (Y) of employees at the Office of the Ministry of Maritime Affairs and Fisheries (Class 1 Fish Quarantine, Quality Control and Fishery Product Safety Agency). The method used in this research is a quantitative approach with descriptive presentation. Determining the population and sampling techniques used in this research used the Census method, the data collection techniques used were observation, interviews, questionnaires and documentation, and the analysis method used was the path analysis method. The results of the first test show that the variables work facilities (X1) and work load (X2) simultaneously have a positive and significant effect on job satisfaction (Y) of employees at the Office of the Ministry of Maritime Affairs and Fisheries (Class 1 Fish Quarantine, Quality Control and Fishery Product Safety Agency ) which is 0.683 or 68.3%. The results of testing the second hypothesis show that work facilities (X1) partially have a positive and significant effect on job satisfaction (Y) of employees at the Office of the Ministry of Maritime Affairs and Fisheries (Fish Quarantine, Quality Control and Safety of Fishery Products Class 1) namely 0.680 or 68 .0%. The results of the third test show that workload (X2) partially has a positive and significant effect on job satisfaction (Y) of employees at the Office of the Ministry of Maritime Affairs and Fisheries (Fish Quarantine, Quality Control and Safety of Fishery Products Class 1) namely 0.203 or 20.3 %.